rTMS Improves Generalized Anxiety Disorder Compared with Sham Treatment - Nierengarten, Mary Beth (MD Conference Express, 2014)
Preliminary data indicate that repetitive transcranial magnetic stimulation (rTMS) is superior to a sham treatment for patients with generalized anxiety disorder (GAD). This article presents the results of an ongoing randomized controlled trial to assess the efficacy of rTMS versus sham treatment for patients with moderate to severe GAD.